The story of rich : a financial fable of wealth and reason during uncertain times / J D Joyce, Matt Joyce. - Joyce, J. D.,1967-
An investing story that provides insights into dealing with your money and finding financial securityMaking the right investment decisions and executing an effective financial plan can be difficult, especially in today s markets. But with the right guidance you can achieve this goal. Now, in Financial Crossings, leading wealth manager John "J.D." Joyce shows you how. Based on his real-world experiences with investors throughout his successful career, this book offers meaningful advice about financial planning and investing.Designed for those with significant assets who are nearing or recently retired, as well as individuals who have recently come into new money through business or inheritance, Financial Crossings skillfully explains financial planning and investing through a fable of a man who sells a business he s worked so hard to build, and now finds himself with more money then he s ever had to deal with.